Proposals to Modify the PRGF-HIPC Trust Instrument : Further Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This follow-up paper focuses on the proposed modifications to HIPC Initiative policy as implemented in the Fund, building on the July paper. It also addresses the key policy issues raised by Executive Directors at the July informal briefing and lays out the modalities and decision required to implement the proposed changes. If adopted, these modifications would also apply to future similarly situated pre-decision point HIPCs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet